RISET AUDIENS SEBAGAI DASAR STRATEGI BRANDING KONSERVASI UNIVERSITAS NEGERI SEMARANG - Riki Arswendi (Jurnal Ilmiah Komunikasi Makna, 2013)
Audience research as a basis for conservation branding strategy is a follow up of previous research on public response to the State University of Semarang conservation policy for failing communicated by the organization to an audience. Research through the identification of aspects of geography, socio-demographic, psychographic, and lifestyle of the people in the audience Sekaran, Semarang State University are expected to use appropriate communication strategies in communicating various conservation programs that aim can be achieved.Keyword: Audience riset, branding,conservation